Ends of the earth : land art to 1974 - Kaiser, Philipp; Kwon, Miwon; Museum of Contemporary Art (Los Angeles, Calif.) (Los Angeles, California : The Museum of Contemporary Art, Los Angeles ; Munich, Germany ; London, United Kingdom ; New York, NY : Distributed by Prestel, 2012)
"The fascinating and generously illustrated catalogue documents the history of Land art from its emergence during the early 1960s through 1974. A companion volume to the first large-scale exhibition on Land art, this book traces the emergence of the artistic impulses to use the earth as material, land as medium, and to locate works in remote sites, beyond familiar art contexts. Ends of the Earth challenges many myths about Land art-that it was primarily a North American phenomenon, that it was foremost a sculptural practice, and that it exceeds the confines of the art system. Essays by leading young scholars will offer new insights into Land art's emergence, including its intrinsic connection to media, its dreams of an elsewhere, the attraction of wastelands, and the problems inherent in a historical evaluation of site-specific or ephemeral art. The book will also include a series of reflections from the major curators, critics, and dealers who helped to make Land art both as work and discourse in the 1960s and 1970s"--
"This catalogue to accompany the museum exhibition traces the emergence of the artistic impulses to use the earth as material, land as medium, and to locate works in remote sites, beyond familiar art contexts. Significantly, "Ends of the Earth" challenges many myths about Land art--that it was primarily a North American phenomenon, that it was foremost a sculptural practice, and that it exceeds the confines of the art system. Featuring over 100 artists hailing from countries including Great Britain, Germany, Iceland, Israel, Japan, the Netherlands, and the United States, the exhibition constitutes the most comprehensive survey of Land art to date"--
This publication accompanies the exhibition "Ends of the Earth: Land Art to 1974," organized by Philipp Kaiser and Miwon Kwon and presented at The Museum of Contemporary Art, Los Angeles, The Geffen Contemporary at MOCA, 1 April-30 July 2012.
Includes bibliographical references (pages 255-261).
boek